Contrast-Induced Acute Kidney Injury in Radiology: Recent Insights and Advances - Bassam Alkhalifah (Journal of Pharmacy and Bioallied Sciences)
Contrast-induced acute kidney injury (CI-AKI) continues a critical concern in the realm of radiology, necessitating constant updates and insights to inform clinical practices. This comprehensive literature review explores the latest advancements and research trends surrounding CI-AKI, shedding light on its multifaceted complexities. By amalgamating the latest findings, this review not only enhances the current knowledge base but also acts as a guiding beacon for healthcare professionals. Ultimately, the insights presented here serve as a valuable resource, fostering continuous improvements in CI-AKI prevention, patient safety, and the overall efficacy of radiological interventions.